Metal in biological samples from electronic cigarette users and those exposed to their second-hand aerosol: a narrative review - Batista, Diane Rezende; Coelho, Liana Sousa; Tanni, Suzana Erico; de Godoy, Irma (Frontiers in Medicine, 2024)
Introduction: Electronic nicotine delivery systems (ENDS) are becoming gradually more popular, particularly in today's youth. Despite being marketed as safe by the tobacco industry, the notable absence of regulation in their composition is evident. Both the fluids and aerosol generated exhibit a wide variety of substances that are not yet fully identified. In addition to additives, the aerosol contains metals, the presence of which can be attributed to the excessive heating of the metallic filaments used in vaporizing the liquid.The aims of this review were to identify and describe studies that have assessed metal levels in biological samples taken from electronic cigarette users and those exposed to their secondhand aerosol. This involved detailing the types and concentrations of metals identified and the biological sample in which the metals were detected.Methods: Two independent researchers conducted searches in the MEDLINE and EMBASE databases to identify studies that measured metal levels in human non-invasive biological samples from electronic cigarette users and secondhand exposure. Data were presented as a narrative review.Results: Eighteen articles were included in this review. Overall active and passive exposure to ENDS were related to higher levels of many metals, mainly lead and cadmium, in biological samples. ENDS users, in general, present lower metal concentrations in bio samples compared to combustible cigarette users.The exposure to primary and secondhand e-cigarette aerosol is related to higher metal concentrations in the biological samples. The adverse effects of this exposure for long-term users are still to be determined.